The Effect of Work Safety and Health on Employees Performance Moderated by Job Satisfaction at PT. SS - Denty Munikartiningsih Ahnas Putri; Dudung Hadiwijaya; Ismail Marzuki (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to determine and analyze the extent to which job satisfaction moderates the effect of work safety and health on employee performance at PT. SS. The method used is associative with a quantitative approach, employing moderation regression analysis. The sample size is 92 individuals, and data analysis was conducted using moderation regression tests, the coefficient of determination, and hypothesis significance testing (t-test). The results of the study indicate that work safety and health have a significant impact on employee performance at PT. SS. Therefore, the company must implement work safety and health measures. However, job satisfaction does not moderate the effect of work safety and health on employee performance. Job satisfaction has not strengthened the impact of work safety and health on performance, meaning the rates of workplace accidents and occupational diseases have not been reduced by the interaction of job satisfaction with work safety and health on employee performance.